2007
DOI: 10.1075/sll.10.2.04jan
|View full text |Cite
|
Sign up to set email alerts
|

The equative sentence in Finnish Sign Language

Abstract: It is argued in this paper that equative sentences in Finnish Sign Language (FinSL) conform to the general schema of (NP) NP+(PI+)NP, parenthesis marking optionality of elements. With respect to this schema, it is further argued, (a) that the function of the first NP in equative sentences is always topic; (b) that topics are marked syntactically, prosodically, and morphologically in FinSL; (c) that the preferred organisation of equative sentences in general is topic-comment; (d) that there are two structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…It contains subtle or reduced CA used with the predicate. 14 14 The sign glossed as PI is a modal element expressing certainty that can be used in equative sentences, see Jantunen (2007). POPULATION-REGISTER is here marked as P. The analysis is based on the fact that the modification of the indicating verb and CA are motivated by the location of the referent in question.…”
Section: Omission With Constructed Action Representing the Agentmentioning
confidence: 99%
“…It contains subtle or reduced CA used with the predicate. 14 14 The sign glossed as PI is a modal element expressing certainty that can be used in equative sentences, see Jantunen (2007). POPULATION-REGISTER is here marked as P. The analysis is based on the fact that the modification of the indicating verb and CA are motivated by the location of the referent in question.…”
Section: Omission With Constructed Action Representing the Agentmentioning
confidence: 99%
“…3 However, nods have been found in FinSL utterances similar to the one presented above in (1). Jantunen (2007) observed that head nods occur in equative sentences, which are assertive utterances with naming, defining, and identifying functions, such as the sentence in (4) (Jantunen 2007:123; 'ews' = eyes widened/squinted; 'brw' = brows raised/wrinkled; 'b' = blink). Jantunen notes that it is difficult to draw any overall conclusions about the syntactic function of the head nod because of its ambiguity.…”
Section: Nod and Noddingmentioning
confidence: 99%
“…mouthing and mouth gestures, which have been investigated (Pimiä 1987;Rainò 2001). There are also a few single references to other non-manual cues in FinSL, such as the articulation of the head in different functional sentence types (Rissanen 1985) or in equative sentences (Jantunen 2007); the articulation of the head and face in interrogative and negative constructions (Savolainen 2006); and head or body movements and eye gaze in role shift (Rissanen 1992;Luckasczyk 2008). Recently, the study of non-manuals in FinSL has started to include the detailed analysis of the activity of the head (Puupponen 2012;Puupponen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such a structure, without pre-and post-core slots, is displayed schematically in Figure 1 (Jantunen 2007, following Van Valin & LaPolla 1997. Such a structure, without pre-and post-core slots, is displayed schematically in Figure 1 (Jantunen 2007, following Van Valin & LaPolla 1997.…”
Section: The Clause In Finslmentioning
confidence: 99%
“…Clauses with an identifying nominal predicate -that is, equative clauses (e.g., The capital of Finland is Helsinki) -have also been investigated in FinSL (Jantunen 2007(Jantunen , 2009. This work has shown that FinSL uses no copula between the nonpredicating and predicating NPs.…”
Section: Clauses With a Nominal Nucleusmentioning
confidence: 99%